Numerical simulation analysis of influence of depth on crack turning behavior in hydraulic fracturing of gas-bearing coal seam - ZHAO Wei; YUAN Yuan; WANG Kai; XU Chao; SONG Yanan; FENG Zhongkai; GUO Xiaofang; WANG Liuyi (Meikuang Anquan, 2022)
As the depth increases, the ratio of horizontal to vertical stress on the coal rock strata will gradually decrease, which affects the crack propagation behavior around hydro-fracture injection hole. In order to explore the characteristics of hydro-fracture crack turning behavior at different depths, based on the mechanical model and adsorption and desorption model of coal seam, COMSOL was used to analyze the stress distribution and crack initiation pressure around the injection hole at different depths. The results show that at shallow depths, the ratio of horizontal stress to vertical stress is greater than 1, the cracks extend mainly horizontally, and the fracture is more likely to turn when the stress ratio increases. At a deeper depth, the ratio of horizontal stress to vertical stress is less than 1, the cracks extend mainly vertically, and the fracture is more likely to turn when the stress ratio decreases.